A biotinylated piperazine-rhodol derivative: a 'turn-on' probe for nitroreductase triggered hypoxia imaging. Issue 2 (14th December 2016) - Zhou, Ying; Bobba, Kondapa Naidu; Lv, Xue Wei; Yang, Dan; Velusamy, Nithya; Zhang, Jun Feng; Bhuniya, Sankarprasad
Abstract : We developed a nitroreductase responsive theranostic probe1 ; it comprises biotinylated rhodol in conjunction with p -nitrobenzyl functionality. Abstract : We developed a nitroreductase responsive theranostic probe1 ; it comprises biotinylated rhodol in conjunction with p -nitrobenzyl functionality. The probe1 showed a remarkable fluorescence 'turn-on' signal in the presence of nitroreductase under physiological conditions. The probe is considerably stable within a wide biological pH range (6–8) and also is very sensitive toward a reducing micro-environment e.g. liver microsome. Further, it enables providing cellular and in vivo nematode images in a reducing microenvironment.